Artemis fowl the Arctic incident - Colfer, Eoin (New York : Talk Miramax Books : Hyperion Books for Children, 2002)
In order to free his father from the Russian Mafiya, Artemis must join forces with the fairy police and his familiar nemesis, Captain Holly Short.
Sequel to: Artemis Fowl.
Sequel: Artemis Fowl: the eternity code.
670L
Keywords: Fowl, Artemis (Fictitious character) -- Juvenile fiction; Fairies -- Fiction; Kidnapping -- Fiction; Magic -- Fiction; Mothers and sons -- Fiction; Science Fiction; England -- Fiction; Children's stories